2023
DOI: 10.3389/fpsyg.2023.1095073
|View full text |Cite
|
Sign up to set email alerts
|

The effect of students’ online learning experience on their satisfaction during the COVID-19 pandemic: The mediating role of preference

Abstract: IntroductionDuring the peak of the COVID-19 pandemic, nearly all educational institutions globally had to eventually embrace the maneuver of transferring to nearly 100% online learning as a new routine for different curricula. Although many students in developing countries such as Kenya are only experiencing the exclusive online learning approach for the first time, research on students’ experience and satisfaction with COVID-19-imposed online learning is largely lacking. Thus, this study examined the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 98 publications
2
0
1
Order By: Relevance
“…digital tool activities for learning. These results align with previous research suggesting that interactive and engaging educational platforms can effectively enhance students' understanding of complex subjects [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…digital tool activities for learning. These results align with previous research suggesting that interactive and engaging educational platforms can effectively enhance students' understanding of complex subjects [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…96 These findings are also similar to those reported in a study conducted in Bahrain where students and faculty members were more satisfied with face-to-face learning and preferred this mode of learning and teaching over e-learning in this situation. 97 Similar findings have been seen in Kenya, 98 Jordan, 17 Tukey 99 and India. 100 However, other studies have reported that students experienced more satisfaction with online learning during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 80%
“…Our research data show that HE students, both at the Bachelor's and Master's degree level, prefer online lectures and traditional face-to-face seminars as opposed to the research carried out by Li et al (2023) emphasises on the choice of traditional teaching by 80% over 20% for online learning. Aziz & Ansari (2021) also add that 62% of students expressed satisfaction with online learning.…”
Section: Discussioncontrasting
confidence: 65%